2006
DOI: 10.1111/j.1365-2966.2006.10649.x
|View full text |Cite
|
Sign up to set email alerts
|

1.4-GHz polarimetric observations of the two fields imaged by the DASI experiment

Abstract: We present results of polarization observations at 1.4 GHz of the two fields imaged by the DASI experiment (α= 23h30m, δ=−55° and α= 00h30m, δ=−55°, respectively). Data were taken with the Australia Telescope Compact Array with 3.4‐arcmin resolution and ∼0.18‐mJy beam−1 sensitivity. The emission is dominated by point sources, and we do not find evidence for diffuse synchrotron radiation even after source subtraction. This allows to estimate an upper limit of the diffuse polarized emission. The extrapolation to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The case of a slope α=−3.5 is also reported for the S/N < 2 region (yellow shaded). For comparison, the plot shows CMB spectra for three different values of r = T / S , the synchrotron emission detected in the two low emission areas in the target fields of the BOOMERanG ( C B BOOM , Carretti et al 2005b) and BaR‐SPOrt experiments ( C B BaR , Carretti et al 2006), and the upper limit found in the DASI fields ( C B DASI , Bernardi et al 2006). Finally, the general contamination at high Galactic latitude, as estimated by the WMAP team using 74.3 per cent of the sky, is also reported: the spectrum at 22.8 GHz is considered (Page et al 2006) and extrapolated to 70 GHz.…”
Section: Implication For Cmbp B‐mode and Discussionmentioning
confidence: 99%
“…The case of a slope α=−3.5 is also reported for the S/N < 2 region (yellow shaded). For comparison, the plot shows CMB spectra for three different values of r = T / S , the synchrotron emission detected in the two low emission areas in the target fields of the BOOMERanG ( C B BOOM , Carretti et al 2005b) and BaR‐SPOrt experiments ( C B BaR , Carretti et al 2006), and the upper limit found in the DASI fields ( C B DASI , Bernardi et al 2006). Finally, the general contamination at high Galactic latitude, as estimated by the WMAP team using 74.3 per cent of the sky, is also reported: the spectrum at 22.8 GHz is considered (Page et al 2006) and extrapolated to 70 GHz.…”
Section: Implication For Cmbp B‐mode and Discussionmentioning
confidence: 99%
“… C B WMAP is the general contamination at high Galactic latitude, as estimated by the WMAP team using an ∼75 per cent sky fraction at 22.8 GHz (Page et al 2007). Spectra measured in small areas selected for their low emission are also shown: the target fields of the experiments BOOMERanG ( C B BOOM , Carretti et al 2005b) and BaR‐SPOrt ( C B BaR ; Carretti et al 2006a) and the upper limit found in the two fields of the experiment DASI ( C B DASI ; Bernardi et al 2006). Finally, C S/N<2 shows the estimate of the emission in the best 15 per cent of the sky (Carretti et al 2006b; the shaded area indicates the uncertainties), while C DRAO the values found in some intermediate regions using 1.4‐GHz data (La Porta et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A full-sky absolutely-calibrated polarization map at 1.4 GHz with 0.5 • resolution was recently published by Wolleben et al (2006). Selected regions of low total intensity synchrotron emission have been observed between 1.4 and 2.3 GHz (Bernardi et al 2003;Carretti et al 2005a;Carretti et al 2005b;Carretti et al 2006;Bernardi et al 2006) characterizing the spatial properties of the diffuse polarized emission down to arcmin scales with the purpose of studying the contamination of the cosmic microwave background polarization.…”
Section: Introductionmentioning
confidence: 99%